Isolating and recording 7 species of fungi associated with the Eastern River Shrimp Macrobrachium nipponense (De Haan, 1849) from the fish ponds in the Garmat Ali campus ,Basra-Iraq - Bader, Sana Q.; Ahmed, Huda K. (Iraqi Journal of Aquaculture, 2021)
Study on Eastern River shrimp Macrobrachium nipponense in earthen ponds for raising fish in Garmat Ali campus ,Basrah , for the period of March to April 2013. Used four different ways to isolate the fungi of shrimp and diagnosed 7 species of Aspergillus flavus , A.niger, Aspergillus sp., A.terreus , Alternaria sp., Penicillium notatum and P. chrysogenum belong three genus of the fungus Aspergillus ,Alternaria and Penicillium. Statistical analysis showed significant differences between the number of diagnosed fungi isolates of each species in different insulation methods , and differences found in the number of isolates of each species of fungi among March and April. The study confirmed that the presence of pathological fungi Aspergillus and Penicillium have a large impact on shrimp diseases fungal infection, especially when the culture conditions are not appropriate.